Agribusiness competitiveness and sustainability - Bacani, Senen C.; Manalili, Nerlita M. ;Sajise, Percy E. (Los Baños, Laguna, Philippines : SEAMEO, SEARCA, 1996)
This book is a product of two seminars that SEARCA sponsored as part o its continuing commitment to effect a more focused strategy for agribusiness development and, consequently, agro-industrial development.
Toward a globally competitive Agribusiness Sector by Senen C. Bacani -- Agro-Industrialization Research and Development: Agribusiness Development Perspective -- Global Competitiveness and sustainable agricultural and Rural Development.
Includes bibliographical references.
Keywords: AGRICULTURE -- ECONOMIC ASPECTS